Alzheimer’s - Chee, Jessice; Kim, Valerie; Yang, Bob (The Meducator, 2018)
Alzheimer’s disease is an age-related neurodegenerative disorder characterized by gradual cognitive decline. With 44 million people affected worldwide, it is one of society’s most prevalent denegerative diseases. The number of Canadians suggering from Alzheimer’s or a related form of dementia is estimated to double to around 1.3 million people within the next generation. This could be due to the repercussions of chronic stress over longer life expectancies.